2020
DOI: 10.1210/endocr/bqaa089
|View full text |Cite
|
Sign up to set email alerts
|

LXRα Phosphorylation in Cardiometabolic Disease: Insight From Mouse Models

Abstract: Abstract Posttranslational modifications, such as phosphorylation, are a powerful means by which the activity and function of nuclear receptors such as LXRα can be altered. However, despite the established importance of nuclear receptors in maintaining metabolic homeostasis, our understanding of how phosphorylation affects metabolic diseases is limited. The physiological consequences of LXRα phosphorylation have, until recently, been studied only in vitro or nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Even though both C57BL/6J mice and ApoE-/-mice are representative animal models of dyslipidemia and heart dysfunction [39,40]. In this study, we chose to feed C57BL/6J mice with a high fat high cholesterol diet to explore the preventive effect of nutraceuticals, to simulate the normal process of the formation of dyslipidemia in hu-man being.…”
Section: Discussionmentioning
confidence: 99%
“…Even though both C57BL/6J mice and ApoE-/-mice are representative animal models of dyslipidemia and heart dysfunction [39,40]. In this study, we chose to feed C57BL/6J mice with a high fat high cholesterol diet to explore the preventive effect of nutraceuticals, to simulate the normal process of the formation of dyslipidemia in hu-man being.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we also found differential expressions of NR1H3 in cholesterol metabolism downstream. NR1H3 is a key gene regulating LXR α. Liver X receptor α (LXR α) is a sterol-regulated transcription factor, which plays an important role in atherosclerosis by integrating cholesterol homeostasis and immunity [50]. Studies have shown that disrupting LXR α phosphorylation can regulate atherosclerosis by inducing macrophage proliferation [51].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cholate serves as a ligand for the nuclear hormone receptor FXR, which regulates the expression of various genes involved in lipoprotein metabolism. Among these genes, apoCII and apoCIII could potentially account for the reduced levels of plasma triglycerides observed in diets that incorporate cholate, in comparison to diets lacking cholate (Voisin et al, 2020).…”
Section: Dietary Modelsmentioning
confidence: 99%